Find the distance \( (d) \) between the pair of points \((6, -1)\) and \((6, -2)\).
Identify the coordinates
The coordinates of the two points are \((x_1, y_1) = (6, -1)\) and \((x_2, y_2) = (6, -2)\).
Apply the distance formula
The distance formula is:
\[
d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}
\]
Substitute the values into the formula
Substitute \(x_1 = 6\), \(y_1 = -1\), \(x_2 = 6\), and \(y_2 = -2\) into the formula:
\[
d = \sqrt{(6 - 6)^2 + (-2 - (-1))^2}
\]
Simplify the expression
Simplify the expression:
\[
d = \sqrt{0^2 + (-1)^2} = \sqrt{0 + 1} = \sqrt{1}
\]
Calculate the final distance
The final distance is:
\[
d = 1
\]
The distance is \(\boxed{1}\) unit(s).
The distance between the points \((6, -1)\) and \((6, -2)\) is \(\boxed{1}\) unit(s).